2011
DOI: 10.1017/s1366728911000125
|View full text |Cite
|
Sign up to set email alerts
|

Age of acquisition and proficiency in a second language independently influence the perception of non-native speech

Abstract: Sensorimotor processing in children and higher-cognitive processing in adults could determine how non-native phonemes are acquired. This study investigates how age-of-acquisition (AOA) and proficiency-level (PL) predict native-like perception of statistically dissociated L2 categories, i.e., within-category and between-category. In a similarity task, participants rated the level of similarity between pairs of English syllables from 1 (similar) to 4 (dissimilar). Early L2 acquisition predicts accurate within-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(51 citation statements)
references
References 38 publications
4
46
0
1
Order By: Relevance
“…This ability to differentiate between L1 and L2 contrasts may be explained by children's acute perception of within-category and between-category phonemes. It has been found that early bilingual adults are able to ignore the irrelevant acoustic differences that exist between exemplars of the same phonemic L2 sound (e.g., hat – hat) and able to distinguish the phonetically meaningful differences that exist between exemplars of different L2 sounds (e.g., hat-hot) (Archila-Suerte et al, 2011). Even though the development of non-native speech perception in early bilinguals may not be linear (Bosch & Sebastián-Gallés, 2005), monolinguals and early bilinguals share a similar perceptual ability in the discrimination of speech sounds (Mayo, Florentine, & Buus, 1997).…”
Section: 1 Early Acquisition In L2 Speech Perceptionmentioning
confidence: 99%
See 2 more Smart Citations
“…This ability to differentiate between L1 and L2 contrasts may be explained by children's acute perception of within-category and between-category phonemes. It has been found that early bilingual adults are able to ignore the irrelevant acoustic differences that exist between exemplars of the same phonemic L2 sound (e.g., hat – hat) and able to distinguish the phonetically meaningful differences that exist between exemplars of different L2 sounds (e.g., hat-hot) (Archila-Suerte et al, 2011). Even though the development of non-native speech perception in early bilinguals may not be linear (Bosch & Sebastián-Gallés, 2005), monolinguals and early bilinguals share a similar perceptual ability in the discrimination of speech sounds (Mayo, Florentine, & Buus, 1997).…”
Section: 1 Early Acquisition In L2 Speech Perceptionmentioning
confidence: 99%
“…However, it has been demonstrated that a high L2 proficiency level predicts improved perception of between-category speech sounds (Archila-Suerte et al, 2011). That is, highly proficient bilinguals can learn to distinguish between two phonemes of different L2 categories (e.g., hat-hot), especially if the L2 sound is markedly different from any L1 sound (Best et al, 2001; Fox, Flege, & Munro, 1995; Iverson et al, 2003).…”
Section: 1 High Language Proficiency In L2 Speech Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the framework of critical period, later L2 onset age is often associated with lower L2 performance due to the maturational decay of the ability to acquire language and/or the interference of the existing linguistic system (Archila-Suerte, Zevin, Bunta, & Hernandez, 2012;Archila-Suerte, Zevin, & Hernandez, 2015;Birdsong & Molis, 2001;Newport, 1990). Although a decline in L2 capability has been demonstrated in morphology, phonology, semantics, and syntax through adulthood (Flege, Yeni-Komshian, & Liu, 1999;Johnson & Newport, 1989;Weber-Fox & Neville, 1996), age six or seven is widely thought as the general turning point and thus the cut-off between early and late bilinguals (Meisel, 2004, chap.…”
Section: Introductionmentioning
confidence: 99%
“…Maturation then proceeded at the same level until the age of 30. This issue could provide evidence for the fact that only very early bilingualism (at approximately age 2) leads to native-like L2 acquisition (Goorhuis-Brouwer & de Bot, 2010) and to accurate phonetic production (Archila-Suerte et al, 2012). In sum, these studies explain sensitive periods in terms of brain development and functions.…”
Section: Discussionmentioning
confidence: 85%